Long-term fatigue after perimesencephalic subarachnoid haemorrhage in relation to cognitive functioning, mood and comorbidity. Issue 9 (24th April 2017) - Boerboom, Wendy; van Zandvoort, Martine J. E.; van Kooten, Fop; Khajeh, Ladbon; Visser-Meily, Johanna M. A.; Ribbers, Gerard M.; Heijenbrok-Kal, Majanka H.
Abstract: Purpose: To study relationships between fatigue and objective and subjective cognitive functioning, mood and comorbidity in the long term after perimesencephalic subarachnoid haemorrhage (PM-SAH). Methods: Cross-sectional study. Objective cognitive functioning was measured with: Trail Making Test; Symbol Substitution; D2; Verbal and Semantic Fluency; Tower Test; Digit Span; 15-Words Test; Rey Complex Figure. Subjective cognitive functioning: Cognitive Failure Questionnaire. Fatigue: Fatigue Severity Scale. Mood: Hospital Anxiety and Depression Scale. Results: Forty-six patients, mean age 50.4 (SD = 9.4), mean time after PM-SAH 4.7 (SD = 1.6) years participated. Patients with fatigue (33%) had significantly lower scores than patients without fatigue on most objective cognitive functioning tests ( p < 0.05). Fatigue score was significantly associated with subjective and objective cognitive functioning, mood and comorbidity. After adjustment for mood and comorbidity, fatigue remained associated with attention and executive functioning. Conclusions: This study supports our previous findings that a third of patients with PM-SAH experience fatigue and problems of cognitive functioning, also in the long term. Future research should investigate whether these patients would benefit from long-term follow-up and/or cognitive rehabilitation programmes. Implications for Rehabilitation: Consequences for patients with PM-SAH are underestimated. One in every three patients suffered from fatigue in the long term after onset of PM-SAH. Patients with PM-SAH should be screened for problems of cognitive functioning, fatigue and mood in outpatient clinic just as patients with aneurysmal SAH.